Association between mental health and HPV in American women: an analysis based on the 2005–2016 NHANES database - Xu Yu; Jingya Nie; Lifang Zhou; Yubin Mao; Yanping Jiang (Journal of Psychosomatic Obstetrics and Gynecology)
Background Human papillomavirus (HPV) is one of the most prevalent sexually transmitted infections (STIs). Individuals with depression face higher risks of other STIs; however, the relationship between depression and HPV remains unclear.Objective To investigate the association between depression and HPV among American women.Methods Data were sourced from the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2016. We employed weighted logistic regression models to explore the relationship between depression scores, depressive states, depression severity and HPV infection risk. The stability of intergroup relationships was assessed by subgroup analyses.Results Seven thousand and twenty-four American women were included, including 3138 HPV-positive individuals. Logistic regression analyses revealed a significant positive correlation between increased depression scores (OR = 1.02, 95% CI: 1.00–1.03, p = .009) and the presence of depression (OR = 1.33, 95% CI: 1.07–1.65, p = .010) with HPV infection risk. The HPV infection risk was elevated in the moderate depression group (OR = 1.32, 95% CI = 1.02–1.70, p = .036). Subgroup analyses indicated that marital status, body mass index and sexual activity frequency interacted with the relationship between depression and HPV (p-interaction < .05).Conclusions Our findings highlight an association between depression and increased HPV infection risk among American women, underscoring the importance of enhancing HPV protection awareness among women with depression.